A methodological investigation into the roots of the resurrection plant, Xerophyta viscosa, for further proteomic analyses - Kamies, Rizqah (Department of Molecular and Cell Biology, 2015)
In order to conduct proteomic analysis on the hydrated root tissues of the resurrection plant, Xerophyta viscosa Baker, aeroponically grown plant roots were subjected to various proteomic techniques. Three protein extraction methods were investigated, of which one method, was the most suited in isolating total protein from the root tissues of X. viscosa.